Errata: Communications - Scientific Letters of the University of Zilina, 21(1), 2019, Passsenger Ride Comfort and International Roughness Index Specifications in the Slovak Republic, p. 15-22. - Mucka, Peter; Stein, George Juraj; Tobolka, Peter (Communications - Scientific Letters of the University of Zilina, 2019)
Errata: Communications - Scientific Letters of the University of Zilina, 21(1), 2019, Passsenger Ride Comfort and International Roughness Index Specifications in the Slovak Republic, p. 15-22.
Keywords: Errata: Communications - Scientific Letters of the University of Zilina; 21(1); 2019; Passsenger Ride Comfort and International Roughness Index Specifications in the Slovak Republic; p. 15-22.